Mediating effect of digital skills in the relationship between academic competence and employability of procurement and supplies professionals - Meshack Siwandeti; Veneranda Rutainurwa; Baraka Israel (International Journal of Academe and Industry Research)
The increasingly digital transformation of procurement highlights the need for an in-depth understanding of the joint effect of digital skills (DGSK) and academic competence (ACCP) on the employability of procurement and supply professionals (EPSP). This study aimed to examine the mediating effect of DGSK in the relationship between ACCP and perceived EPSP in Tanzania, using the theoretical framework of Social Cognitive Career Theory (SCCT). Data for the study were collected from 307 respondents, comprising chief executive officers (CEOs) and human resource managers (HRMs) from public and private institutions in Dodoma, Tanzania, using a cross-sectional questionnaire survey. Structural equation modelling (SEM) was employed to test the study's hypotheses. The study's notable findings are that ACCP has a significant positive effect on both DGSK and EPSP. Furthermore, DGSK has a significant positive effect on EPSP, simultaneously mediating the impact of ACCP on EPSP. Drawing on SCCT, the study reveals that DGSK serves as a strategic belief and self-efficacy mechanism through which procurement and supply professionals can translate their ACCP into improved employability. Among other implications, this study suggests that academic institutions, policymakers, and regulators should reform curricula to mandate DGSK in procurement training through internships, apprenticeships, digital upskilling workshops, and hands-on e-procurement courses led by field and ICT experts. Empirically, the study advances existing literature on employability dynamics by highlighting the critical role of DGSK as a bridge between theoretical knowledge and practical job readiness in the digital era of procurement.